Humoral Epitope Spreading in Autoimmune Bullous Diseases - Didona, Dario; Di Zenzo, Giovanni (Frontiers in Immunology, 2018)
Autoimmune blistering diseases are characterized by autoantibodies against structural adhesion proteins of the skin and mucous membranes. Extensive characterization of their autoantibody targets has improved understanding of pathogenesis and laid the basis for the study of antigens/epitopes diversification, a process termed epitope spreading (ES). In this review we have reported and discussed ES phenomena in autoimmune bullous diseases and underlined their functional role in disease pathogenesis. A functional ES has been proposed: 1) in bullous pemphigoid patients and correlates with the initial phase of the disease, 2) in pemphigus vulgaris patients with mucosal involvement during the clinical transition to a mucocutaneous form; 3) in endemic pemphigus foliaceus, underlining its role in disease pathogenesis and 4) in numerous cases of disease transition associated to an intermolecular diversification of immune response. All these findings could give useful information to better understand autoimmune disease pathogenesis and to design antigen/epitope specific therapeutic approaches.